Collected Works of C.G. Jung, Vol. 18, The Symbolic Life: Miscellaneous Writings - Jung, C. G. (Carl G. Jung: Collected Works of C. G. Jung, 1977)
This volume is a miscellany of writings that Jung published after the Collected Works had been planned, minor and fugitive works that he wished to assign to a special volume, and early writings that came to light in the course of research